PENGARUH PERSEPSI KEMUDAHAN, MANFAAT DAN KEAMANAN TERHADAP KEPUTUSAN PEMBELIAN KARTU INDOMARET DI REST AREA KM 35 SENTUL KABUPATEN BOGOR - Adyas, Dasmansyah; Ainurahmah, Rika (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2019)
The research method used is multiple linear regression analysis method, using simultaneous tests and partial test. The data used are primary and secondary data . Samples taken as many as 96 respondents using purposive sampling technique. The results of this study indicate that perceptions of ease, perceptions of benefits and perceptions of security, physical evidence, processes jointly influence the decision to purchase Indomaret cards by 0.406 or 40% ease, benefits and security is one of the processes of positive influence on consumer decisions. In partial test (t-test) it is known significantly with sig. Respectively 0,000 and 0,001 <from 0,05 and t count value respectively 3,703,> t table values ​​1,66159, 1,787 and 3,588> t table values ​​1,66159. This shows that the variable perceived ease of use, perceived usefulness and security influence consumer decisions in purchasing Indomaret cards.